2019
DOI: 10.3389/fnins.2019.01380
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Dependent Regulation of Sleep Dynamics in a Network Model of the Sleep–Wake Cycle

Abstract: Sleep is a fundamental homeostatic process within the animal kingdom. Although various brain areas and cell types are involved in the regulation of the sleep-wake cycle, it is still unclear how different pathways between neural populations contribute to its regulation. Here we address this issue by investigating the behavior of a simplified network model upon synaptic weight manipulations. Our model consists of three neural populations connected by excitatory and inhibitory synapses. Activity in each populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(84 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, FA in CC did not contribute reliably, which indicates that the subjective sleep-wake disturbances may predominantly be linked to other WM networks, compared to the actigraphy measures. Our result may reflect the notion that different aspects of sleep-wake regulation potentially is linked to specialized and differentiated neuronal circuits and corresponding structural networks ( Héricé and Sakata, 2019 ). Sleep-wake regulation involves a complex network including different brain regions and neurotransmitters, and studies have identified that specific damages on different parts of this network result in various types of sleep-wake disturbances ( Schwartz and Roth, 2009 ; Brown et al, 2012 ; Scammell et al, 2017 ).…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, FA in CC did not contribute reliably, which indicates that the subjective sleep-wake disturbances may predominantly be linked to other WM networks, compared to the actigraphy measures. Our result may reflect the notion that different aspects of sleep-wake regulation potentially is linked to specialized and differentiated neuronal circuits and corresponding structural networks ( Héricé and Sakata, 2019 ). Sleep-wake regulation involves a complex network including different brain regions and neurotransmitters, and studies have identified that specific damages on different parts of this network result in various types of sleep-wake disturbances ( Schwartz and Roth, 2009 ; Brown et al, 2012 ; Scammell et al, 2017 ).…”
Section: Discussionsupporting
confidence: 73%